Molecular detection of benzimidazole resistance in Haemonchus contortus of sheep in Punjab - SINGH, EKTA; KAUR, PARAMJIT; SINGLA, L D; SANKAR, M; BAL, M S (The Indian Journal of Animal Sciences, 2020)
Single nucleotide polymorphism (SNP) at codon 167, 198 and 200 of Î²-tubulin isotype 1 gene accounts for benzimidazole resistance in Haemonchus contortus. To assess the anthelmintic resistance to benzimidazole group, allele specific polymerase chain reaction (AS-PCR) was employed on 50 adults of local abattoir of Ludhiana and 138 harvested larvae of H. contortus from faecal samples collected from field flocks of 6 districts of western zone of Punjab. The adults were found to be homozygous resistant (rr) showing 100% prevalence of resistant allele (r). AS-PCR on 138 larvae collected from different districts of Punjab showed 49.28% (69) homozygous resistant (rr), 3.62% (5) homozygous susceptible (SS) and 46.37% (64) heterozygous (rS) population. Species was confirmed as H. contortus by PCR-RFLP from the three fragments of size 462 bp, 211 bp and 147 bp. The pioneer study on the molecular diagnosis of benzimidazole resistance in H. contortus showed an overall allele frequency for resistant and susceptible population to be 0.72 (TTC) and 0.28 (TAC), espectively indicating development of high level of resistance in sheep.